Apoptosis in the skeletal muscle of patients with heart failure: investigation of clinical and biochemical changes. Issue 4 (1st October 2000) - Vescovo, G; Volterrani, M; Zennaro, R; Sandri, M; Ceconi, C; Lorusso, R; Ferrari, R; Ambrosio, G B; Dalla Libera, L
Abstract : OBJECTIVE: To investigate the contribution of apoptosis in the development of the skeletal myopathy in chronic heart failure. DESIGN: The electrophoretic pattern of myosin heavy chains (MHC), fibre cross sectional area, number of in situ nick end labelling (TUNEL) positive apoptotic myocyte nuclei, and the tissue levels of caspase-3, Bcl-2, and ubiquitin were determined in biopsies taken from the vastus lateralis muscle. The study involved nine patients with severe chronic heart failure caused by ischaemic heart disease and hibernating myocardium and five controls. RESULTS: In chronic heart failure patients the vastus lateralis showed a significant increase of MHC2a and MHC2b and a greater degree of fibre atrophy, as demonstrated by the decreased cross sectional area. There was also an increased number of TUNEL positive apoptotic myocyte nuclei. Tissue concentrations of Bcl-2 were decreased, while those of caspase-3 and ubiquitin were increased. Peak oxygen consumption (Vo 2 ) was negatively correlated with the number of TUNEL positive nuclei and the fibre cross sectional area. There was a correlation between the number of apoptotic nuclei and the fibre cross sectional area, but no correlation between myosin heavy chains and number of apoptotic nuclei. CONCLUSIONS: Myocyte apoptosis occurs in the skeletal muscle of patients with chronic heart failure, and its magnitude is associated with the severity of exercise capacity limitation and the degree of muscle atrophy. Muscle atrophy contributes to the limitation of exercise capacity, together with the increased synthesis of fast, more fatiguable myosin heavy chains.